Vocational Teacher Training – Self-Evaluation of Prospective Teachers - Nagyné Kondor, Rita (International Journal of Engineering and Management Sciences, 2020)
Teacher Training Programmes provide teachers of Vocational Education and Training schools.  At the end the training the students wrote self-evaluation about their most significant experiences. The article deals with the self-evaluation of prospective vocational teachers’ progress after their practical pedagogical training in Vocational Education and Training schools. The students reported on their progress in their various skills. According to the results the students believe that practical pedagogical training makes an essential contribution to their education and future profession.